Innovations that could build the food of future - Prokopenko, V. V. (ТДАТУ, 2021)
It's no secret that in the future, humanity will face problems associated with global warming. We will face prolonged periods of heat and drought, followed by large-scale floods. All this does not bode well for particularly favorable conditions for animal husbandry and crop production, and the population of our planet will grow by another two billion people, and everyone will need to be fed with. Scientists are puzzled by the creation of more sustainable vegetables and grains, the development of new technologies and the search for nutritional alternatives.
Keywords: global warming; for nutritional alternatives; bioengineering